Short-Term Plan of Action : Wenchuan Earthquake of 12 May 2008 - World Bank (Washington, DC, 2012)
Recovery and reconstruction 12 May 2008 Mw 8.0 Wenchuan earthquake will involve a large and complex series of programs, for which recent earthquake disasters provide useful lessons, key of which are: (i) the response or stabilization phase will probably be significantly reduced during 20-25 May, during which the recovery phase will scale up and last for several months; (ii) planning for the recovery phase has to start immediately and be based on a sound and comprehensive damage and loss assessment; (iii) housing is a key sector and several crucial decisions will need to be made very soon, primary of which are whether housing reconstruction will be predominantly local, on-site, and owner driven or involve large relocation and more top-down management. Recent experience in Pakistan and Indonesia favors the more local, owner-driven model; and (iv) planning for long-term reconstruction has to begin early in the recovery phase and will involve key policy decisions regarding the creation of an 'earthquake reconstruction authority' or similar agency. This note provides recommended short-term actions by the World Bank for the Government of China, within a framework of good practices in recovery and reconstruction after an earthquake. The World Bank has assisted partner governments in this regard in approximately 60 earthquakes, including most recently the 1999 Marmara (Turkey), 2001 Gujarat (India), 2004 Indian Ocean (India, Indonesia, Sri Lanka, and Thailand), and 2005 South Asia (Afghanistan, India, and Pakistan). Assistance to these countries constitutes the largest disaster-related portfolio of the World Bank.